Plant Derived Phytocompound, Embelin in CNS Disorders: A Systematic Review - Kundap, Uday P.; Bhuvanendran, Saatheeyavaane; Kumari, Yatinesh; Othman, Iekhsan; Shaikh, Mohd. Farooq (Frontiers in Pharmacology, 2017)
A CNS disease is the one which affects either the spinal cord or brain and causing neurological or psychiatric complications. During the 19th century, modern medicines have occupied the therapy for many ailments and are widely used these days. Herbal medicines have often maintained popularity for historical and cultural reasons and also considered safer as they originate from natural sources. Embelin is a plant-based benzoquinone which is the major active constituent of the fruits of Embelia ribes Burm. It is an Indo-Malaysian species, extensively used in various traditional medicine systems for treating various diseases. Several natural products including quinone derivatives, which are considered to possess better safety and efficacy profile, are known for their CNS related activity. The bright orange hydroxybenzoquinone embelin-rich fruits of Embelia ribes have become popular in ethnomedicine. The present systematic review summarizes the effects of embelin on central nervous system and related diseases. A PRISMA model for systematic review was utilized for search. Various electronic databases such as Pubmed, Springer, Scopus, ScienceDirect and Google Scholar were searched between January 2000 and February 2016. Based on the search criteria for the literature, 13 qualified articles were selected and discussed in this review. The results of the report showed that there is a lack of translational research and not a single study was found in human. This report gives embelin a further way to be explored in clinical trials for its safety and efficacy.